2019
DOI: 10.3390/cells9010083
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic Human Liver Extracellular Matrix 3D Scaffolds Promote Smad-Dependent TGF-β1 Epithelial Mesenchymal Transition

Abstract: An altered liver microenvironment characterized by a dysregulated extracellular matrix (ECM) supports the development and progression of hepatocellular carcinoma (HCC). The development of experimental platforms able to reproduce these physio-pathological conditions is essential in order to identify and validate new therapeutic targets for HCC. The aim of this work was to validate a new in vitro model based on engineering three-dimensional (3D) healthy and cirrhotic human liver scaffolds with HCC cells recreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 39 publications
1
56
0
Order By: Relevance
“…Aetiology specific differences have also been observed. Mazza and colleagues report increased collagen 10A, 5A, fibulin 5, and fibronectin in cirrhotic liver from patients with HCC ( 31 ). Whereas, advanced ALD is associated with increased deposition of collagen type 1, upregulated synthesis of osteopontin (OPN) and increased synthesis of cellular fibronectin (cFN).…”
Section: Ecm In Chronic Liver Diseasementioning
confidence: 99%
“…Aetiology specific differences have also been observed. Mazza and colleagues report increased collagen 10A, 5A, fibulin 5, and fibronectin in cirrhotic liver from patients with HCC ( 31 ). Whereas, advanced ALD is associated with increased deposition of collagen type 1, upregulated synthesis of osteopontin (OPN) and increased synthesis of cellular fibronectin (cFN).…”
Section: Ecm In Chronic Liver Diseasementioning
confidence: 99%
“…The phosphorylated Smad2/3 proteins form a complex with common mediator Smad4 and then translocate into the nucleus to regulate TGF-β target gene expression [31][32][33]. Emerging evidence has proven that TGF-β signaling possesses both Smad and non-Smad pathways, and regulated tumorigenesis via different molecular mechanisms, including, TGF-β1/Smad2/3, PI3K-AKT-mTOR, Wnt, Notch, and ERK, p38, and JUN N-terminal kinase (JNK) MAPK pathways [34][35]. Various studies also indicated that TGF-β was signi cantly associated with the expression of MAGs and metabolic reprogramming of cancer [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…56 Omics technologies such as proteomics or singlecell transcriptomics address issues with regards to characterisation of cells and matrices. [139][140][141][142] Novel non-destructive imaging techniques, such as micro-CT, optimal coherence tomography or 2photon microscopy promise to overcome the barrier of increased tissue thickness. [143][144][145] The use of second-harmonic generation or modified amino acids, such as azide-labelled proline, provides an ideal system for visualising matrix modifications.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%